DOP037 Postoperative anti-TNF therapy is associated with a significant reduction of both endoscopic and clinical recurrence following surgery for ileocolonic Crohn's disease: results of a prospective nationwide cohort conducted by the GETAID chirurgie group. (16th January 2018) - Maggiori, L; Brouquet, A; Zerbib, P; Lefevre, J; Denost, Q; Germain, A; Cotte, E; Beyer-Berjot, L; Munoz-Bongrand, N; Desfourneaux, V; Rahili, A; Duffas, J -P; et al.
Abstract: Background: Postoperative recurrence rate following surgery for ileocolonic Crohn's disease (CD) can be up to 60%. Predictive factors of postoperative recurrence remain controversial and have never been evaluated in a large prospective cohort study, leading difficulties regarding patients' risk stratification and indication of postoperative prophylactic treatments. Methods: From September 2013 to September 2015, data on 592 consecutive patients who underwent surgery for ileocolonic CD at 19 academic French centres were collected prospectively in the RICCO registry held by the GETAID chirurgie group. Among them, 346 patients underwent a postoperative ileocoloscopy within 6–12 months following surgery and were included in the present study. Endoscopic recurrence was defined as a Rutgeerts score ≥ i2. Clinical recurrence was defined as a symptomatic (CD activity index score>150) endoscopic recurrence. Results: 12-month postoperative endoscopic and clinical recurrence rates were 57.6 ± 3.4% and 11.3 ± 2.2%, respectively. A total of 173 patients (50%) had a postoperative prophylactic treatment (excluding probiotics, aminosalicylates, and budesonide), including thiopurines in 69 patients (20%) and anti-TNF therapy in 94 patients (27%). In multivariate Cox regression analysis, the absence of postoperative smoking (OR = 0.57; CI 95% = 0.40–0.83; p = 0.004), postoperative prophylactic treatment (OR = 0.49; CI 95% = 0.34–0.71; p < 0.001), and a B3 disease behaviour according to the Vienna classification (OR = 0.59; CI 95% = 0.41–0.85; p = 0.005) were identified as the only independent predictors of reduced endoscopic recurrence rate. Postoperative prophylactic treatment (OR = 0.42; CI 95% = 0.20–0.85; p = 0.016), and a B3 disease behaviour (OR = 0.29; CI 95% = 0.13–0.68; p = 0.004) were identified as the only independent predictors of reduced clinical recurrence rate. Postoperative anti-TNF therapy was associated with a significant reduction of both 12-month endoscopic ( p < 0.001) and clinical ( p = 0.018) recurrence rates. Conclusions: Postoperative prophylactic anti-TNF therapy significantly decreases both endoscopic and clinical recurrence rates following surgery for ileocolonic Crohn disease. This study suggest that upfront surgery followed by postoperative anti-TNF therapy is probably the best therapeutic approach for complex Crohn disease (B3 disease behaviour) with low recurrence rate after surgery.